Ventriculo-bipleural shunt as last resort in a 4-year-old child in whom a VP and VA shunt failed - Ratliff, Miriam; Unterberg, Andreas; Bächli, Heidi (Journal of neurosurgery. Pediatrics, 2016)
The authors present the unusual case of a 4-year-old boy who had a complex history of posthemorrhagic hydrocephalus and who underwent more than 40 surgeries related to this condition. In the course of trying to treat his condition, ventriculoperitoneal, ventriculoatrial, and ventriculopleural shunts were inserted and failed. The child presented with a dysfunction of his shunt system. A ventriculopleural shunt was inserted, but within days the patient developed dyspnea as a clinical symptom of pleural effusion that required repeated thoracentesis. A bipleural drainage system was inserted, and no relevant pleural effusions developed during the follow-up period. Although the authors’ experience is based on a single case, they do suggest bipleural drainage in patients with clinically relevant pleural effusions when the more common alternatives are not a good choice. Bipleural drainage might particularly be an option in children, who are prone to pleural effusion because of the smaller absorbing pleural surface. The authors reviewed the English-language literature on PubMed dating back to 1952. To their knowledge, this is the only published case in which a patient was treated with a ventriculo-bipleural shunt.
Published online November 27, 2015
Gesehen am 17.06.2020